Contemporary tectonic stress pattern of the Taranaki Basin, New Zealand - Rajabi, M.; Ziegler, M.; Tingay, Mark; Heidbach, O.; Reynolds, S. (Wiley-Blackwell Publishing, 2016)
The present-day stress state is a key parameter in numerous geoscientific research fields including geodynamics, seismic hazard assessment, and geomechanics of georeservoirs. The Taranaki Basin of New Zealand is located on the Australian Plate and forms the western boundary of tectonic deformation due to Pacific Plate subduction along the Hikurangi margin. This paper presents the first comprehensive wellbore-derived basin-scale in situ stress analysis in New Zealand. We analyze borehole image and oriented caliper data from 129 petroleum wells in the Taranaki Basin to interpret the shape of boreholes and determine the orientation of maximum horizontal stress (SHmax). We combine these data (151 SHmax data records) with 40 stress data records derived from individual earthquake focal mechanism solutions, 6 from stress inversions of focal mechanisms, and 1 data record using the average of several focal mechanism solutions. The resulting data set has 198 data records for the Taranaki Basin and suggests a regional SHmax orientation of N068°E (±22°), which is in agreement with NW-SE extension suggested by geological data. Furthermore, this ENE-WSW average SHmax orientation is subparallel to the subduction trench and strike of the subducting slab (N50°E) beneath the central western North Island. Hence, we suggest that the slab geometry and the associated forces due to slab rollback are the key control of crustal stress in the Taranaki Basin. In addition, we find stress perturbations with depth in the vicinity of faults in some of the studied wells, which highlight the impact of local stress sources on the present-day stress rotation.